DYNAMIC PARAMETER VALUE OF THE GAS GENERATOR WATER SAVING SYSTEMS - Abramov, Y.; Kryvtsova, V.; Mikhailyuk, A. (Municipal economy of cities. Series: «Economy science», 2022)
The method for determining the dynamic parameter of the main element of the water saving system and the supply of water, the gas generator, has been developed. Expanding the method of orienting to the selection in the algorithm for controlling the technical station of the gas generator, the system for saving and supplying water, which is in its own place, is the storage system for fire prevention. The method is based on a mathematical description of the amplitude-frequency characteristics of the gas generator of the system for saving and supplying water, in which, in an obvious way, there is a functional fallacy of the dynamic parameter of such a gas generator. In the capacity of the primary information of one hundred hundred hourly power of the gas generator of the system for saving and supplying water, there is information of one hundred and fifty hourly characteristics - a transitional function. An experimental way is used to form an array of data, which is designed to encourage a mathematical description of the frequency response of the gas generator of the system for saving and supplying water, which is realized by a numerical way. The grounding of the mathematical description of the amplitude-frequency characteristics of the gas generator of the system for saving and supplying water is based on the least squares method. In this case, a mathematical description of the frequency response of the gas generator of the system for saving water supply in the standard form is obtained. The method of determining the dynamic parameter of the gas generator of the water supply saving system includes the sequence of mutual procedures and orientations to the graphical method of developing transcendental alignment, which will be based on the least squares method. To confirm the reliability of the obtained results, a test task is verified.